Sistem Informasi Pemasaran dengan Penerapan CRM (Customer Relationship Management) Berbasis Website menggunakan Metode Waterfall dan Agile - Johar Saputra Irsandi; Iskandar Fitri; Novi Dian Nathasia (KITA Institute, 2021)
Bella Frame ART shop is a business shop that is engaged in selling paintings, calligraphy, and frames. Until now, the promotion method still uses brochures, posters, and pamphlets, so shop owners need a lot of money to convey information to a broad target market. Storing the results of feedback, or messages from customers is also needed, in order to assist the store in making decisions in product marketing and customer service in the future. With the application of CRM in the website-based marketing information system at the Bella Frame ART Shop, data storage can be stored neatly and in detail, and delivery of product information to customers can be done more easily and quickly and is expected to help the store make decisions in marketing products and customer service for the future. In this study, the authors used application development methods, namely the waterfall and agile methods. Web-based information systems with the proposed Customer Relationship Management (CRM) method are systems that meet the needs and have the advantage of being integrated with systems related to marketing information systems. As well as using the waterfall method can help writers in the first stage of application development because testing is carried out after the application has been run while the agile method is used at a later stage so that it can cover deficiencies in the first stage of application development, namely requests for changing needs so that applications can continue to be developed despite requests needs change and application testing can continue at any time so that errors or bugs can be found more easily.